Epidermal growth factor receptormutations in lung adenocarcinoma in Malaysian patients - Liam, Chong Kin; Abdul Wahid, Mohamed Ibrahim; Rajadurai, Pathmanathan; Cheah, Yoke Kqueen; Ng, Tiffany Shi Yeen (Lippincott, Williams & Wilkins, 2013)
INTRODUCTION: Despite available data from other Asian countries, the prevalence of epidermal growth factor receptor (EGFR) mutations among lung adenocarcinoma patients has not been reported in Malaysia. This study sought to determine the frequency of EGFR mutations among multiethnic Malaysian patients diagnosed with lung adenocarcinoma. METHODS: Demographic and clinical information of patients whose lung adenocarcinoma biopsy specimens were submitted for EGFR mutation testing at Sime Darby Medical Center from 2009 to 2011 were analyzed. EGFR mutations at exons 18, 19, 20, and 21 were detected either through bidirectional sequencing or real-time polymerase chain reaction. RESULTS: Among 812 patients in the study, 49% were female, 63.7% were ethnic Chinese, 29.4% Malay, 4.8% Indian, and 2.1% other ethnic groups. Mutations were present in the tumors of 321 patients (39.5%), with mutations at exons 19 (23.5%) and 21 (14.9%) being the most common. Mutations were significantly more frequent among women than in men (52.5% versus 27.8%, p < 0.001). Although mutations were more common among Chinese (40.8%) compared with Malay (37.2%) or Indian (33.3%) patients, the difference was not statistically significant (p = 0.591). Of 211 patients with smoking history records, never-smokers had a higher mutation rate compared with ever-smokers (54.8% versus 20.7%, p < 0.001). CONCLUSION: EGFR mutations were present in 39.5% of patients. Mutations were more common in women and never-smokers with no differences in mutation frequency between different ethnicities. Because of the high mutation rates, reflex testing for EGFR mutation should be a routine practice for advanced lung adenocarcinoma patients in Malaysia.